KONSTRUKSI SOSIO-RELIGIUS UMAT HINDU DI BALI PADA MASA COVID-19 - I Wayan Sukrayasa (UHN IGB Sugriwa Denpasar, 2021)
The social order and religious behavior in Indonesia, especially in Bali, have undergone many changes due to fluctuations in the Covid-19 pandemic. In addition to the impact on health, it also touches on the socio-religious behavior of Hindus in Bali. This religious perspective has a very strong influence in making people aware, especially Hindus in Bali, to take certain actions, including in dealing with the Covid-19 outbreak. This is also a very difficult challenge to the lives of Hindus, especially in Bali during this pandemic, namely when holding yajna ceremonies. Some changes in the behavior of Hindus are examples of the stages of outpouring or human self-expression into a world that is much different from the period before the Covid-19 pandemic. This has certainly rebuilt the social life and religiosity of Hindus in Bali during the Covid-19 pandemic. This article uses a qualitative approach by applying a descriptive analytical method. The construction process of behavior and social life of Hindus in Bali during the Covid-19 Pandemic, when viewed from the perspective of Berger & Luckman's theory, took place through dialectical social interactions of three forms which became the entry concept, namely objective reality, symbolic reality and subjective reality. Regarding the Covid-19 pandemic situation, in terms of the religiosity of Hindus in Bali, the implementation of the yajna ritual should be carried out in a simple way, but still guided by the provisions of the Vedic scriptures.